PCW-1001, a Novel Pyrazole Derivative, Exerts Antitumor and Radio-Sensitizing Activities in Breast Cancer - Kang, Minsung; Pandit, Navin; Kim, Ah-Young; Cho, Suk Joon; Kwon, Young-Ju; Ahn, Jiyeon; Lee, Kyu Myung; Wu, Sangwook; Oh, Jeong Su; Jung, Kwan-Young; Kim, Jae-Sung (Frontiers in Oncology, 2022)
As pyrazole and its derivatives have a wide range of biological activities, including anticancer activity, the design of novel pyrazole derivatives has emerged as an important research field. This study describes a novel pyrazole derivative that exerts antitumor and radiosensitizing activities in breast cancer both in vitro and in vivo. We synthesized a novel pyrazole compound N,N-dimethyl-N'-(3-(1-(4-(trifluoromethyl)phenyl)-1H-pyrazol-4-yl)phenyl)azanesulfonamide (PCW-1001) and showed that it inhibited several oncogenic properties of breast cancer both in vitro and in vivo. PCW-1001 induced apoptosis in several breast cancer cell lines. Transcriptome analysis of PCW-1001-treated cells showed that it regulates genes involved in the DNA damage response, suggesting its potential use in radiotherapy. Indeed, PCW-1001 enhanced the radiation sensitivity of breast cancer cells by modulating the expression of DNA damage response genes. Therefore, our data describe a novel pyrazole compound, PCW-1001, with antitumor and radiosensitizer activities in breast cancer.